Tuftsin: A Natural Molecule Against SARS-CoV-2 Infection - Huang, Jiahao; Wang, Jing; Li, Yan; Wang, Ziyuan; Chu, Ming; Wang, Yuedan (Frontiers in Molecular Biosciences, 2022)
Coronavirus disease 2019 (COVID-19) continuously progresses despite the application of a variety of vaccines. Therefore, it is still imperative to find effective ways for treating COVID-19. Recent studies indicate that NRP1, an important receptor of the natural peptide tuftsin (released from IgG), facilitates SARS-CoV-2 infection. Here, we found 91 overlapping genes between tuftsin targets and COVID-19-associated genes. We have demonstrated that tuftsin could also target ACE2 and exert some immune-related functions. Molecular docking results revealed that tustin could combine with ACE2 and NRP1 in stable structures, and their interacted regions cover the binding surfaces of S1-protein with the two receptors. Using surface plasmon resonance (SPR) analysis, we confirmed that tuftsin can bind ACE2 and NRP1 directly. Importantly, using SPR-based competition assay we have shown here that tuftsin effectively prevented the binding of SARS-CoV-2 S1-protein to ACE2. Collectively, these data suggest that tuftsin is an attractive therapeutic candidate against COVID-19 and can be considered for translational as well as clinical studies.